Central Neural Correlates During Inhibitory Control in Lifelong Premature Ejaculation Patients - Yang, Xuejuan; Gao, Ming; Zhang, Lan; Liu, Lin; Liu, Peng; Sun, Jinbo; Xi, Yibin; Yin, Hong; Qin, Wei (Frontiers in Human Neuroscience, 2018)
Lifelong premature ejaculation (LPE) is a common male sexual dysfunction. Lack of active control for rapid ejaculation brought great distress to sexual harmony, and even fertility. Previous neurophysiology studies revealed an ejaculation-related control mechanism in the brain. However, it remains unclear whether this inhibitory network is altered in LPE patients. The present study investigated the central inhibitory network function of LPE patients by using stop signal task-related functional magnetic resonance imaging and resting-state functional connectivity analysis. The results showed no difference in task-related behavioral performance or neural activation during response inhibition between LPE patients and controls. However, LPE patients showed a significantly different correlation pattern between the stop signal reaction time (SSRT) and left inferior frontal gyrus activation during successful inhibition, in which a typical negative correlation between SSRT and the activation was completely disappeared in patients. In addition, using the left inferior frontal gyrus as a seed, patients showed weaker functional connectivity between the seed and two areas (left dental nucleus and right frontal pole) compared with controls. These data suggest that LPE patients have an abnormal brain control network, which may contribute to the reduced central control of rapid ejaculation. This study provides new insights into the neural mechanism of LPE involving the central inhibitory network, which may offer an underlying intervention target for future treatment.